Studi Metodologi Tafsir Hassan Hanafi - Devi Muharrom Sholahuddin (Studia Quranika, 2016)
Muslims Classical interpretation is no longer considered relevant to the epoch and Muslims today. A theory that considered to be capable of responding to the needs of current times is hermeneutics. One of the figures who uses these theories is Hasan Hanafi. He saw the works of the classical interpreters cannot answer the problems of mankind today caused by the invalidity of their methods which have two major faults, which are orientation and epistemological. He offers a hermeneutical approach to address these two issues. He did this by using the social theory and phenomenology of Edmund Husserl when reading the text of the Qur’an. Social approach intends not only to follow the context of the text, but instead, the reality of deducing the meaning of the text. The theory of Phenomenology gives more freedom for the interpreter to read the text